Words of wisdom : a philosophical dictionary for the perennial tradition - Carlson, John W. (Book collections on Project MUSE., 2012)
Words of Wisdom offers precise definitions of well over a thousand key philosophical terms, richly cross-referenced, with special reference to the Catholic and Thomistic traditions.